Effects of exercise interventions on cancer-related fatigue and quality of life among cancer patients: a meta-analysis - Xiaoli Chen; Juejin Li; Chongcheng Chen; Yalin Zhang; Shu Zhang; Yun Zhang; Lin Zhou; Xiaolin Hu (BMC, 2023)
Abstract Purpose In this study, exercise interventions were evaluated for their effects on cancer-related fatigue (CRF) and quality of life (QoL) among cancer patients. Design A meta-analysis was performed. Methods We systematically searched the PubMed/Medline, Web of Science, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), PsycINFO, and CINAHL databases, and gray literature sources including the Virginia Henderson International Nursing Library and Google Scholar. This study only included randomized controlled trials (RCTs) examining how exercise interventions affect CRF and QoL among cancer patients. Based on the Cochrane Risk-of-Bias Assessment Tool, version 2 (RoB 2) and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach, the methodological quality of the included studies was evaluated. In addition, standardized mean differences (SMDs) and 95% confidence intervals (CIs) were applied to assess the intervention effect with respect to CRF and QoL. Data analysis was performed using Review Manager (version 5.4). Results There were a total of 1573 participants in the 28 included articles. According to the meta-analysis, CRF (SMD = -0.35, 95% CI: -0.63 to -0.07, p = 0.01) and QoL (SMD = 0.36, 95% CI: 0.20 to 0.53, p < 0.01) were positively affected by exercise interventions. Subgroup analyses revealed considerable improvements in CRF (SMD = -0.54, 95% CI: -1.00 to -0.09, p = 0.02) and QoL (SMD = 0.38, 95% CI: 0.16 to 0.59, p < 0.01) from aerobic exercise. An intervention duration less than 12 weeks had a better effect on CRF (SMD = -0.80, 95% CI: -1.43 to -0.17, p = 0.01) and QoL (SMD = 0.53, 95% CI: 0.21 to 0.85, p < 0.01), and three times per week was the most effective frequency in improving QoL (SMD = 0.69, 95% CI: 0.28 to 1.11, p < 0.01). Exercise intervention was more successful in improving CRF (SMD = -0.66, 95% CI: -1.10 to -0.21, p < 0.01) and QoL (SMD=-0.50, 95% CI: 0.23 to 0.78, p < 0.01) in female cancer patients. Sensitivity analyses showed that the pooled outcomes were reliable and stable. Conclusion Exercise interventions are a workable approach to improve CRF and QoL among cancer patients. An aerobic exercise intervention of less than 12 weeks might be most effective in improving CRF and QoL, and three times per week might be the most appropriate frequency. Exercise might have a more positive effect on improving CRF and QoL in female cancer patients. Additionally, a larger number of high-quality RCTs should be conducted to further confirm the efficacy of exercise interventions on CRF and QoL among cancer patients. Registration number CRD42022351137.